Duodenal GIST Presenting as Large Pancreatic Head Mass: An Uncommon Presentation - Singh, Sumitoj; Paul, Surinder; Khandelwal, Pawan; Khichy, Sudhir (JOP. Journal of the Pancreas, 2012)
Context Duodenal gastrointestinal stromal tumors (GIST) are uncommon. They usually present with gastrointestinal bleed, upper abdominal pain or mass abdomen. Tumor arising from the second part of duodenum can be wrongly diagnosed as pancreatic mass. Case report We present a case of a thirty-year-old male who came with chief complaint of mass upper abdomen. On laparotomy there was a 15x10 cm mass arising from the whole of anterior surface head of pancreas and was attached with the second part of duodenum for about 1-2 cm only. Patient underwent pancreaticoduodenectomy and histopathology revealed that tumor was arising from the duodenal wall. Conclusion Duodenal gastrointestinal stromal tumors can grow exophytically into large mass and involve the pancreas without infiltrating microscopically and present as pancreatic head mass. Image: Macroscopic appearance of resected specimens showing tumor attached mainly along the pancreatic head.